A Semantic Study of TikTok Post Captions from a Generation Z Language Perspective - Anjung Kinanthi Dewi (Raja Zulkarnain Education Foundation, 2025)
This study emphasizes the analysis of contextual meaning in captions in TikTok posts, with a primary focus on the use of language typical of Generation Z. This study applies a descriptive qualitative method through a contextual semantic approach. Data sources were obtained from TikTok video captions that were deliberately selected based on the characteristics of the language style and frequency of use using observation guidelines as a data collection tool. The results of the study revealed that fifteen terms frequently used by Generation Z are fomo, mood, notice, kalcer, skena, vibes, denial, clingy, sus, spam, yapping, flexing, cupu, mager, and megalodon. These fifteen terms used by Generation Z have contextual meanings that cannot always be explained lexically. The discussion shows that these fifteen terms function as a means of expressing identity, emotion, and social interaction that are typical in digital communication. Therefore, TikTok captions act as a linguistic medium that reflects the creativity, performativity, and social identity of Generation Z, while also becoming a link between generations in today's digital culture.